การประยุกต์ใช้อักษรโดดในอัล-กุรอาน ในการจัดการเรียนการสอน - มันยุนุ, มูฮามัสสกรี (Al-HIKMAH Journal, 2018)
The Qur’an is the main reference source of knowledge throughout Islam history. In the Book, everything essential to human beings is described. Its content covers various sciences: belief principles, religious practices, daily life activity, science, history, education, etc. Divine teachings in the Qur’an are various in types and methods appropriate to necessity and human cognitive capability. This paper aims to put forward recommendations for applying Quranic isolated letters to teaching. It is apparent that a divine technique of isolated letters in the Qur’an for teaching human beings is effective. A great number of people willingly convert to Islam through reading the Qur’an and realize the truth in it. The isolated letters in the beginning of some Surahs (chapter) is an instructional technique effectively attracting the audience to the truth according to the letters. This technique is an introduction stage successfully applied by the Prophet Muhammad (pbuh) to Islam propagation in the early period. As his followers, teachers are required to learn about and apply it to the class or anywhere.